Inventing politics : a new political anthropology of the Hawaiian kingdom - Mykkänen, Juri, 1964- (University of Hawaii Press, 2003)
How did early nineteenth-century foreigners understand Hawaiian chiefly politics? What kinds of cultural resources did Hawaiians themselves have to make sense of their own structures of domination and those of the West? What was the outcome in political terms of the encounter between Hawaiians and foreigners? To answer these questions, this volume takes readers on an ethnographic journey through Hawaii's early contact period. It begins by exploring the translation work done by American Protestant missionaries, who played a central role in bridging cultural differences between Hawaiians and Westerners. Evangelicalism and liberal capitalism set the stage for constructing political images of a "pagan" society, and the present work follows the subsequent evolution and transformation of these images. Inventing Politics is a theoretical statement of a new kind of political anthropology. Through an extensive use of primary sources, including many contemporary Hawaiian-language newspapers and dictionaries, it argues that what informs our current understanding of politics was already present in the early nineteenth-century encounters between Hawaiians and foreigners--a reading that translates seemingly apolitical events into the language of politics and speaks to the fundamental question of whether politics is a functional aspect of every society or an invention based on specific cultural meanings and interests